Gry interdyskursywne w rosyjskojęzycznych parodiach politycznych - Agata Jankowicz (Studia Rossica Posnaniensia)
Political parodies transcend the prevailing social hierarchies, opening the field for polemics with government representatives. They also provide a space for the contamination of two or more distant discourses. In their texts, parodists refer to the rules of creating texts and utterances of political discourse, while modifying their selected elements by means of interdiscursive games. The purpose of the study is to define the category of the interdiscursive game and to analyze its strategies based on the example of contemporary Russian parodies on political issues published on YouTube. The study examines interdiscursive games grouped according to the following classification: genre convention games, intertextual games, games at the level of different linguistic means, structural games involving extralinguistic signs. As a result of the analysis, parodic interdiscursive games were divided into two categories: first-degree references and further references. The references of the first degree consist in transferring the main imitated discourse to the discourse of the comic. The second type of games concerns parodic references to other discourses that are introduced to the main imitated discourse. Interdiscursive games of both types help to discover the mechanisms that shape the political discourse. Thus, parody, using borrowed schemes, reveals those meanings which were not expressed explicitly in the original texts and utterances.